Решите систему уравнений методом замены переменной​


Решите систему уравнений методом замены переменной​

taniamishanina taniamishanina    2   12.12.2020 17:56    0

Ответы
112811281128 112811281128  11.01.2021 18:03

\left \{ {{x=-1-y} \atop {y^{2} -7x-7}} \right. \\y^{2} -7(-1-y)=7\\y=0\\y=-7\\x=-1-o\\x=-1(-7)\\x=-1\\x=6\\(x_{1} ,y_{1} )=(-1,0)\\(x_{2} ,y_{2} )=(6,-7)\\\left \{ {{-1+0=-1} \atop {0^{2}-7*(-1)=7\\ }} \right. \\\left \{ {{6-7=-1} \atop {(-7)^{2}-7*6=7 }} \right. \\\left \{ {{-1=-1} \atop {7=7}} \right.\\\left \{ {{-1=-1} \atop {7=7}} \right. \\(x_{1} ,y_{1} )=(-1,0)\\(x_{2} ,y_{2} )=(6,-7)\\Пошаговое объяснение:

ПОКАЗАТЬ ОТВЕТЫ